Correlation of Hemostatic Parameter with Lung Tumor Marker in Non-Small Cell Lung Cancer Patient with Chemotherapy - Ganda M. Leonard Samosir; Parluhutan Siagian; Putri Chairani Eyanoer (Jurnal Respirologi Indonesia, 2018)
Backgrounds: There is a subclinical activation of coagulation and ﬁbrinolysis system in patient with lung cancer. Alterations in hemostatic system are seen frequently in lung cancer correlated with the prognosis of disease. In oncology practice, the use of tumor markers may be helpful in the diagnosis and pathologic classification of tumors. Tumor marker may reflect both, stage of the disease and prognosis. Aim of this research is to asses the correlation of this parameters in patient non-small cell lung cancer with chemotherapy. Methods: This research is an analytic observational with a cross sectional design. The research was conducted at RSUP Haji Adam Malik, Medan from January 1, 2015 to May 31, 2016. Blood test examination was performed to measure the hemostatic parameter (PT, INR, APTT, TT, D-dimer) and serum tumor marker (CEA, Cifra21-1, NSE) of 41 non-small cell lung cancer patients before first cycle of chemotherapy and after fourth or sixth cycles of chemotherapy. Results: The study comprised 41 patients of non-small cell lung cancer (31 adenocarcinoma, 10 squamous cell carcinoma), There were 35 men (85,4%) and 3 women (14,6%) with mean age of 56,7 years. For all patients, we give a platinum based therapy as first line chemotherapy (gemsitabine and carboplatin regimen in 27 patients, paclitaxel and carboplatin in 10 patients, vinorelbine and carboplatin in 4 patients). There is no significant difference of hemostatic parameter and serum tumors marker values before chemotherapy againts after chemotherapy values. And there is a weak negative correlation of hemostatic parameter againts serum tumor marker on non-small cell lung cancer patients with chemotherapy. Conclusion: There is a weak negative correlation of hemostatic parameter againts serum tumor marker in non-small cell lung cancer patients with chemotherapy. (J Respir Indo 2018; 38(1): 33-38)